Physical Activity and Bone Health: What Is the Role of Immune System? A Narrative Review of the Third Way - Lombardi, Giovanni; Ziemann, Ewa; Banfi, Giuseppe (Frontiers in Endocrinology, 2019)
Bone tissue can be seen as a physiological hub of several stimuli of different origin (e.g., dietary, endocrine, nervous, immune, skeletal muscle traction, biomechanical load). Their integration, at the bone level, results in: i) changes in mineral and protein composition and microarchitecture and, consequently, in shape and strength; ii) modulation of calcium and phosphorous release into the bloodstream, iii) expression and release of hormones and mediators able to communicate the current bone status to the rest of the body. Different stimuli are able to act on either one or, as usual, more levels. Physical activity is the key stimulus for bone metabolism acting in two ways: through the biomechanical load which resolves into a direct stimulation of the segment(s) involved and through an indirect load mediated by muscle traction onto the bone, which is the main physiological stimulus for bone formation, and the endocrine stimulation which causes homeostatic adaptation. The third way, in which physical activity is able to modify bone functions, passes through the immune system. It is known that immune function is modulated by physical activity; however, two recent insights have shed new light on this modulation. The first relies on the discovery of inflammasomes, receptors/sensors of the innate immunity that regulate caspase-1 activation and are, hence, the tissue triggers of inflammation in response to infections and/or stressors. The second relies on the ability of certain tissues, and particularly skeletal muscle and adipose tissue, to synthesize and secrete mediators (namely, myokines and adipokines) able to affect, profoundly, the immune function. Physical activity is known to act on both these mechanisms and, hence, its effects on bone are also mediated by the immune system activation. Indeed, that immune system and bone are tightly connected and inflammation is pivotal in determining the bone metabolic status is well known. The aim of this narrative review is to give a complete view of the exercise-dependent immune system-mediated effects on bone metabolism and function.